Analisis Bauran Pemasaran pada Pembelian Produk Perawatan Kulit Bersertifikasi Halal - Hasan, Sawqi Saad El (https://jurnal.binamandiri.ac.id/, 2021)
This study aims to examine the relevance of the 4P marketing mix theory (price, promotion, product, and place) to consumer purchases of halal-certified skincare products. This study targets one hundred respondents as research samples in the DKI Jakarta area, and the desired age is between eighteen and sixty years. Halal-certified skincare products in this study are limited to facial and body skincare products, such as facial cleansers, face creams, masks, moisturizers, body lotions, scrubs, to lip care. The method in this research is multiple linear regression. This study indicates that the dominant factor influencing consumer purchases of halal-certified skincare products is the product factor. The result shows that good and quality products can increase purchases. Quality products indirectly influence consumers in their decision to buy halal-certified skincare products. A convenient location and not far from the center of consumer activity will indirectly be the choice of consumers in buying halal-certified skincare products. Thus, the results of this study prove that consumer attitudes built on product quality would be able to affects purchases.